2022
DOI: 10.21203/rs.3.rs-2146111/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High prevalence of uncontrolled hypertension among patients with early chronic kidney disease attending tertiary hospitals in Dodoma, Tanzania

Abstract: Background The prevalence of uncontrolled hypertension has been increasing globally including Sub-Saharan Africa (SSA) accelerating the burden of chronic kidney disease (CKD), cardiovascular diseases (CVD) and non-communicable diseases (NCDs). Methods A cross-sectional study was conducted among adult patients with early-stage CKD attending the medical outpatient department (MOPD) clinics of two tertiary hospitals in Dodoma between November 2020 to March 2021. Descriptive and inferential statistics were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(39 reference statements)
0
0
0
Order By: Relevance
“…Univariate analysis revealed several factors associated with an increased risk of uncontrolled hypertension, including older age, male sex, a higher BMI, and the presence of comorbidities such as diabetes, dyslipidemia, chronic kidney disease, smoking status, and alcohol consumption. These findings are consistent with previous studies that reported similar associations [ 15 , 16 ].…”
Section: Discussionsupporting
confidence: 94%
“…Univariate analysis revealed several factors associated with an increased risk of uncontrolled hypertension, including older age, male sex, a higher BMI, and the presence of comorbidities such as diabetes, dyslipidemia, chronic kidney disease, smoking status, and alcohol consumption. These findings are consistent with previous studies that reported similar associations [ 15 , 16 ].…”
Section: Discussionsupporting
confidence: 94%